Evaluation of the antimutagenic and anticarcinogenic effects of inulin in vivo - Mauro, M. O. [UNESP]; Monreal, M. T F D; Silva, M. T P [UNESP]; Pesarini, J. R. [UNESP]; Mantovani, M. S.; Ribeiro, L. R. [UNESP]; Dichi, J. B.; Carreira, C. M.; Oliveira, R. J. (Genetics and Molecular Research, 2013)
The incidence of colorectal cancer is growing worldwide. The characterization of compounds present in the human diet that can prevent the occurrence of colorectal tumors is vital. The oligosaccharide inulin is such a compound. The aim of this study was to evaluate the antigenotoxic, antimutagenic and anticarcinogenic effects of inulin in vivo. Our study is based on 3 assays that are widely used to evaluate chemoprevention (comet assay, micronucleus assay, and aberrant crypt focus assay) and tests 4 protocols of treatment with inulin (pre-treatment, simultaneous, post-treatment, and pre + continuous). Experiments were carried out in Swiss male mice of reproductive age. In order to induce DNA damage, we used the pro-carcinogenic agent 1,2-dimethylhydrazine. Inulin was administered orally at a concentration of 50 mg/kg body weight following the protocols mentioned above. Inulin was not administered to the control groups. Our data from the micronucleus assay reveal antimutagenic effects of inulin in all protocols. The percentage of inulin-induced damage reduction ranged from 47.25 to 141.75% across protocols. These data suggest that inulin could act through desmutagenic and bio-antimutagenic mechanisms. The anticarcinogenic activity (aberrant crypt focus assay) of inulin was observed in all protocols and the percentages of damage reduction ranged from 55.78 to 87.56% across protocols. Further tests, including human trials, will be necessary before this functional food can be proven to be effective in the prevention and treatment of colon cancer. © FUNPEC-RP.
Keywords: Chemoprevention; Fiber; Inulin; 1,2 dimethylhydrazine; DNA; inulin; aberrant crypt focus assay; analytic method; animal cell; animal experiment; antigenotoxic activity; antimutagenic activity; antineoplastic activity; body weight; comet assay; concentration response; DNA damage; drug activity; drug determination; in vivo study; male; micronucleus test; mouse; nonhuman